Establishment of rapid saturation mutagenesis and screening methods for improving the neutralizing activity of monoclonal antibodies - Wu, Xi; Wang, Lijie; He, Chenchen; Shen, Yanru; Wang, Youchun; Huang, Weijin (Frontiers in Immunology, 2025)
BackgroundMonoclonal antibodies have been widely used in the fight against infectious diseases and are recommended for postexposure prophylaxis (PEP) of the rabies virus because of their advantages of easy supply, low cost, and high efficacy. To maximize treatment efficiency and minimize side effects, the binding affinity of isolated mAbs requires further enhancement.MethodsIn this study, we developed a high-throughput saturation mutagenesis platform to improve the neutralizing activity of a preclinical antirabies mAb. We generated a system displaying antibodies on mammalian cell surfaces to block the invasion of the pseudotyped rabies virus. Saturation mutagenesis was performed on the complementarity-determining regions (CDRs) of the parental mAb, followed by screening for mutant mAbs with greater neutralizing activity.ResultsWe identified several mutations, including S5A, K18F, and N29C, that increased the neutralizing activity of the mAbs against six fixed strains of rabies virus, with average improvements of 4.92, 3.45, and 4.99 times, respectively. Furthermore, mAbs with the combined mutations S4I-P35S-N76D and S14H-T32N demonstrated significantly improved neutralizing activity.ConclusionWe established a high-throughput saturation mutagenesis platform for antibody affinity modification, enhancing the anti-infection ability of the antirabies NC08 antibody through single-point and multiple-point mutants. This platform is also applicable for optimizing other mAbs in preclinical stages in terms of neutralizing activity and achieving broad-spectrum activity.